Effect of chemical composition of alfalfa hay on several digestive measurements in growing rabbits - García J.; De Blas C.; Carabaño R.; García P. (Rabbit production in hot climates, 1994)
Seventy five New Zealand White x Californian rabbits were used to study the influence of chemical composition of alfalfa hay on caecal and caecotrophy characteristics in growing rabbits. Five alfalfa hays were selected varying from 387 to 550 g NDF/kg and 35.2 to 27.0 g N/kg DM. Caecum, caecal contents and whole digestive tract weight (percentage of body weight) and caecal NDF increased linearly (P equal to 0.001) with the NDF content of diet. This fact implied the impairment of carcass performance when increased the fibre of diet. A linear decrease with NDF content of diet was observed for caecal N (P equal to 0.001) and ammonia concentration (P equal to 0.024), the lowest value of ammonia concentration. It can be concluded that the variation of chemical composition of alfalfa hays produce a change in variables that indicate fermentation characteristics such as caecal ammonia, VFA and microbial nitrogen concentration. However, this changes do not affect the caecal PH value.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)